(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2013)
In this paper a new class of function called contra-wgrÎ± continuous function is introduced and its properties are studied. Further the notion of almost contra wgrÎ±-continuous function is introduced.